Thermo-physiological and Molecular Profiling of Two Indigenous Purebred Saudi Sheep under Acute Heat Stress Conditions - Samara, E. M.; Bahadi, M. A.; Khan, M. A.; Al-Badwi, M. A.; Abdoun, K. A.; Afzal, M.; Alghamdi, S. S.; Al-Haidary, A. A. (Faculty of Animal Science, IPB University, 2024)
In light of the escalating global concern regarding adaptation and resilience to elevated temperatures due to climate change, this experiment was designed to assess the thermo-physiological attributes of two native sheep breeds (Najdi and Naimi) and to delineate potential genetic factors conferring heat tolerance amidst acute exposure to elevated ambient temperatures. Meteorological and thermo-physiological parameters were scrutinized at distinct intervals (0 min, 30 min, 120 min, 24 hr, and 48 hr), alongside the analysis of heat-responsive gene expression at 0 min, 30 min, and 120 min, following the exposure of nine healthy male lambs from each breed (mean body weight: 25 kg; age: 4 months) to a bio-meteorologically-simulated environment, maintaining an average ambient temperature of 45 °C (approximately 93 units in the temperature-humidity index). In addition, blood samples were collected from each lamb, with total RNA isolated and purity assessed, followed by qRT-PCR analysis of 16 heat stress candidate genes using validated primers and standardized thermocycling protocols, including controls to ensure accuracy. Data were analyzed using statistical methods, including PROC GLM and PROC MEANS in SAS, one-way ANOVA, and pairwise differences with the LSD test for significance, while gene expression differences were calculated using the comparative Ct method and 2^ (−ΔΔCt) for relative quantification. The findings elucidate that the Najdi breed manifests heightened thermotolerance relative to the Naimi breed, as evidenced by diminished indicators of heat stress, encompassing skin temperature, respiratory rate, packed cell volume, adaptability coefficient, serum total protein, glucose levels, and triiodothyronine concentration. Moreover, analysis of gene expression patterns revealed widespread activation of heat stress-responsive genes in both breeds under thermal stress conditions; however, Najdi lambs consistently exhibited elevated expression levels of these genes compared to their Naimi counterparts. Notably, genes including HSP90AB1, HSPB6, HSF1, STIP1, HSP60, HSP90, and HSPB1 demonstrated particularly pronounced upregulation in Najdi lambs. In conclusion, the integrative thermo-physiological and molecular profiling highlights the superior thermotolerance and evolutionary adaptation of the Najdi breed to the hot climate of the KSA, in contrast to the Naimi breed.